Distinct Solid‐Electrolyte‐Interphases on Sn (100) and (001) Electrodes Studied by Soft X‐Ray Spectroscopy. Issue 3 (18th February 2014) - Qiao, Ruimin; Lucas, Ivan T.; Karim, Altaf; Syzdek, Jaroslaw; Liu, Xiaosong; Chen, Wei; Persson, Kristin; Kostecki, Robert; Yang, Wanli
<x xml:space="preserve">Abstract</x> Soft X‐ray absorption spectroscopy with different probe depth was employed to characterize the solid electrolyte interphases (SEIs) formed on β‐Sn single crystals with two different surface orientations. Based on comparative studies of C‐K, O‐K, and F‐K absorption spectra between the SEIs and reference samples, SEI on Sn (100) mainly consists of porous Li2CO3 species with electrolyte uptake, while SEI on Sn (001) essentially consists of LiF and organic molecules, with a small amount of –CO3 and electrolyte buried inside. Theoretical calculation suggests that Sn (001) surface is more reactive than (100), especially after air exposure. The reactive (001) surface facilitates the decomposition of LiPF6 to form a LiF layer. In contrast, SEI on (100) surface is predominately from the typical decomposition of carbonate‐based electrolyte. While the LiF passivates Sn (001) electrode after one cycle, the porous carbonate layer on (100) surface does not prevent further decomposition of electrolyte after many cycles. This leads to drastically different electrochemical behavior and morphology of the two SEIs. The result is a direct proof that surface properties of active materials could strongly impact the SEI formation on electrodes even with the same electrolyte. Such effect could lead to distinct SEI formation and electrochemical performance.